Resin composition and application thereof

By modifying the maleimide prepolymer and combining the active esters and epoxy resin, the problem of poor compatibility between the active esters and maleimide resins is solved, and the heat resistance and overall performance of the resin cured product are improved.

CN119798990AActive Publication Date: 2025-04-11SHENGYI TECH SUZHOU

Patent Information

Application Number
CN202411998795.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-11
Estimated Expiration
2044-12-30

AI Technical Summary

Technical Problem

The compatibility of the active esters and maleimide resins is poor, resulting in agglomeration or turbidity during blending, making it impossible to form a homogeneous resin solution, and the glass transition temperature after curing appears bimodal or multimodal, resulting in poor heat resistance of the circuit substrate.

Method used

By modifying the maleimide prepolymer, the maleimide resin is modified using an amine compound and an allyl compound, and combined with an active ester and an epoxy resin, the content of the low molecular weight components in the modified bismaleimide prepolymer is controlled to improve the compatibility of the resin composition.

Benefits of technology

The heat resistance of the resin cured product is improved, the dielectric properties and water absorption are reduced, and the overall performance of the resin composition is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005227062810000031
    Figure BDA0005227062810000031
  • Figure BDA0005227062810000043
    Figure BDA0005227062810000043
  • Figure BDA0005227062810000052
    Figure BDA0005227062810000052
Patent Text Reader

Abstract

The invention discloses a resin composition and application thereof. The resin composition comprises the following components in parts by solid weight: 20-100 parts of a modified maleimide prepolymer; 10 to 80 parts of epoxy resin; 5-60 parts of active ester; 5-50 parts of an elastomer; reactants of the modified maleimide prepolymer comprise an amine compound, an allyl compound and maleimide resin; in the modified bismaleimide prepolymer, the number average molecular weight is 1t; the mass ratio of the components of 1000 is 10%-40%. The maleimide resin is modified by adopting the amine compound and the allyl compound together, the active ester compound and the epoxy resin are matched, and the content of low-molecular-weight components in the modified maleimide prepolymer is controlled, so that the compatibility among the maleimide resin, the active ester and the epoxy resin is improved; and moreover, the heat resistance of a resin condensate is improved, and the dielectric property and the water absorption rate are reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the technical field of electronic materials, and relates to a resin composition and the application of the resin composition in a prepreg, a laminate, an insulating board, an insulating film, a circuit substrate and an electronic device. Background Art

[0002] With the development and scale-up of 5G, PCB substrate materials need to have a lower dielectric constant and dielectric loss tangent to reduce signal delay, distortion and loss during high-speed transmission, as well as interference between signals.

[0003] Maleimide resin has excellent heat resistance, high modulus, and low CTE, so it is widely used in high-performance printed circuit boards. Active ester resin, as a curing agent, does not produce secondary hydroxyl groups during the curing process with epoxy resin. At the same time, due to its own low polarity, the cured product has a lower dielectric constant and dielectric loss tangent.

[0004] However, active esters and maleimide resins have poor compatibility and are difficult to co-cured. When the two are blended, one of the components will precipitate and aggregate or form a turbid resin solution, and a uniform resin solution cannot be formed. Moreover, after curing, the glass transition temperature of the mixture containing the two will show double or multiple peaks, resulting in problems such as poor heat resistance of the final prepared circuit substrate. Summary of the invention

[0005] The present application provides a resin composition and a prepreg, a laminate, an insulating board, an insulating film, a circuit substrate and an electronic device made from the resin composition.

[0006] To achieve the above application purpose, one embodiment of the present application provides a resin composition, which comprises, by solid weight:

[0007] 20-100 parts of modified maleimide prepolymer;

[0008] 10-80 parts of epoxy resin;

[0009] 5-60 parts of active ester;

[0010] 5-50 parts of elastomer;

[0011] The reactants of the modified maleimide prepolymer include an amine compound, an allyl compound and a maleimide resin; and in the modified bismaleimide prepolymer, the mass proportion of the component with a number average molecular weight <1000 is 10% to 40%.

[0012] By modifying the maleimide resin with amine compounds and allyl compounds, and adding active ester compounds and epoxy resins, and controlling the content of low molecular weight components in the modified maleimide prepolymer, not only the compatibility between the maleimide resin, active ester and epoxy resin is improved, but also the heat resistance of the resin cured product is improved, and the dielectric properties and water absorption are reduced.

[0013] In the modified bismaleimide prepolymer, when the mass proportion of the component with a number average molecular weight <1000 is >40%, phase separation will occur, that is, the bismaleimide resin is separated from the epoxy resin and other resins, the cross-linking density is low, and precipitation is easy, thereby leading to problems such as poor heat resistance and moisture and heat resistance of the resin composition; when the mass proportion of the component with a number average molecular weight <1000 is <10%, there is a phenomenon of poor wettability between the resin and the glass fiber cloth, which leads to a decrease in the adhesion between the substrate and the copper foil, and the heat resistance of the electric furnace substrate will also decrease.

[0014] Preferably, in the modified bismaleimide prepolymer, the mass proportion of the component with a number average molecular weight <1000 is 10%, 15%, 20%, 25%, 30%, 35% or 40%.

[0015] Preferably, in the modified bismaleimide prepolymer, the component with a number average molecular weight <1000 is at least one of an amine-modified maleimide resin, an allyl-modified maleimide resin, and an allyl-amine-modified maleimide resin.

[0016] Preferably, the reactants of the modified maleimide prepolymer include, by solid weight: 1 to 50 parts of the amine compound; 5 to 60 parts of the allyl compound; and 100 parts of the maleimide resin.

[0017] More preferably, the reactants of the modified maleimide prepolymer include, by solid weight: 30 to 50 parts of the amine compound; 5 to 30 parts of the allyl compound; and 100 parts of the maleimide resin.

[0018] Preferably, the preparation method of the modified maleimide prepolymer comprises: dissolving and dispersing the amine compound, the allyl compound and the maleimide resin in an organic solvent, heating to 60°C to 150°C under nitrogen protection and keeping stirring, reacting for 0.5 to 5 hours, to obtain the modified bismaleimide prepolymer.

[0019] As a further improvement of one embodiment of the present application, the reactants of the modified maleimide prepolymer further include 0.5 to 10 parts of an aminophenol compound by solid weight, so as to control the overall reaction rate of the prepolymerization reaction, improve the processability, and improve the comprehensive properties of the cured product.

[0020] Preferably, the aminophenol compound is a p-aminophenol compound, a m-aminophenol compound or an o-aminophenol compound.

[0021] As an optional scheme, the amine compound is selected from at least one of unsubstituted phenylenediamine, methylphenylenediamine, dimethylphenylenediamine, trimethylphenylenediamine, tetramethylphenylenediamine, xylene diamine, diaminopyridine, diaminodiphenylmethane, substituted diaminodiphenylmethane, bis[4-(4-aminophenoxy)phenyl]propane, bis[4-(4-aminophenoxy)phenyl]hexafluoropropane, diaminobenzophenone, diaminodiphenyl ether, diaminodiphenyl sulfone, diaminobiphenyl, diaminodiphenyl sulfide, diaminobinaphthyl, diaminodiphenylfluorene, diaminoanthraquinone, and amino-terminated silicone oil.

[0022] Preferably, the amine compound is selected from at least one of diaminodiphenyl ether, diaminodiphenyl sulfone, diaminodiphenylmethane and amino-terminated silicone oil.

[0023] As an optional solution, the allyl compound is selected from at least one of diallyl bisphenol A, diallyl bisphenol F, diallyl bisphenol S, allyl phenol oxide resin, allyl phenol formaldehyde resin and diallyl diphenyl ether.

[0024] Preferably, the allyl compound is diallyl bisphenol A.

[0025] As an optional solution, the maleimide resin is selected from at least one of the following structures:

[0026]

[0027] Me is methyl, Et is ethyl;

[0028] Me is a methyl group;

[0029] R1 is methylene or ethyl, R2 is hydrogen, methyl or ethyl, and n is an integer from 1 to 10;

[0030]

[0031] n is an integer from 1 to 10;

[0032] n is an integer from 1 to 10;

[0033] R is hydrogen, methyl or ethyl, and n is an integer from 1 to 10;

[0034] R is a methyl group, and n is an integer of 1-20.

[0035] Preferably, the active ester contains an unsaturated double bond. When the active ester contains an unsaturated double bond, a more homogeneous resin glue can be obtained, further improving the comprehensive performance of the resin cured product.

[0036] As an optional solution, the active ester is at least one of the following structures:

[0037]

[0038] Among them, Ar is an aromatic group; Ar1 ​​is an aromatic group and contains an unsaturated double bond substituent.

[0039] Preferably, the Ar group is a residue of a bisphenol structure, and Ar1 is a phenyl group or a naphthyl group containing an unsaturated double bond.

[0040] More preferably, the Ar group is a residue of bisphenol A, bisphenol F, bisphenol S, bisphenol E, dicyclopentadiene bisphenol, biphenyl bisphenol or naphthyl bisphenol.

[0041] Preferably, the bisphenol structure contains allyl or vinyl groups.

[0042] When the active ester is an active ester compound containing a double bond, it has better compatibility with the modified bismaleimide resin containing a double bond.

[0043] As an optional scheme, the epoxy resin is selected from at least one of bisphenol A epoxy resin, bisphenol F epoxy resin, bisphenol S epoxy resin, bisphenol E epoxy resin, phosphorus-containing epoxy resin, o-cresol epoxy resin, bisphenol A novolac epoxy resin, phenol novolac epoxy resin, cresol novolac epoxy resin, triphenylmethane epoxy resin, tetraphenylethane epoxy resin, biphenyl epoxy resin, naphthalene ring epoxy resin, dicyclopentadiene epoxy resin, isocyanate epoxy resin, aralkyl linear phenolic epoxy resin, alicyclic epoxy resin, glycidyl amine epoxy resin, glycidyl ether epoxy resin, and glycidyl ester epoxy resin.

[0044] Preferably, the elastomer is at least one of styrene elastomer, acrylic elastomer, methacrylate elastomer, silicone elastomer, nitrile elastomer and core-shell rubber elastomer.

[0045] Preferably, the styrene elastomer is a hydrogenated or partially hydrogenated styrene-butadiene copolymer.

[0046] As an optional solution, the styrene-based elastomer is at least one of a hydrogenated or partially hydrogenated styrene-butadiene diblock copolymer and a hydrogenated or partially hydrogenated styrene-butadiene triblock copolymer.

[0047] As an optional solution, the acrylic elastomer and the methacrylic elastomer each independently contain at least one of the following structures:

[0048] Wherein, R1 is a C1-C5 alkyl group, and x is an integer from 1 to 100;

[0049] Wherein, R2 is a C1-C5 alkyl group, and y is an integer from 1 to 100;

[0050] Wherein, R3 is hydrogen or methyl, and o is an integer from 1 to 100.

[0051] More preferably, R1 is methyl, and R2 is methyl, ethyl or butyl.

[0052] As an optional solution, the silicone elastomer comprises at least one of the following structures:

[0053]

[0054]

[0055] Wherein, R is a C1-C12 hydrocarbon group or a C1-C12 alkoxy group; X is a mercapto group, an epoxy group, a hydroxyl group, a methoxy group or an amino group.

[0056] Preferably, R is methyl or phenyl.

[0057] Preferably, X is a mercapto group or an epoxy group.

[0058] As a further improvement of one embodiment of the present application, the resin composition further includes 30 to 200 parts of inorganic filler based on solid weight.

[0059] As an optional solution, the inorganic filler is selected from at least one of non-metallic oxides, metal nitrides, non-metallic nitrides, inorganic hydrates, inorganic salts, metal hydrates or inorganic phosphorus.

[0060] Preferably, the inorganic filler is selected from at least one of fused silica, crystalline silica, spherical silica, hollow silica, aluminum hydroxide, aluminum oxide, talc, aluminum nitride, boron nitride, silicon carbide, barium sulfate, barium titanate, strontium titanate, calcium carbonate, calcium silicate, mica, and glass fiber powder.

[0061] More preferably, the inorganic filler is at least one of fused silica, crystalline silica, spherical silica, and hollow silica; more preferably, it is surface-treated spherical silica.

[0062] As a further improvement of one embodiment of the present application, the inorganic filler is surface treated with a silane coupling agent, and the silane coupling agent is an epoxy-containing silane coupling agent, an amino-containing silane coupling agent, a vinyl-containing silane coupling agent, an acrylate-containing silane coupling agent, or an allyl-containing silane coupling agent.

[0063] Preferably, the median particle size of the inorganic filler is 1 to 15 microns, more preferably 1 to 10 microns.

[0064] As a further improvement of one embodiment of the present application, the resin composition further comprises 0.01 to 8 parts of a catalyst based on solid weight.

[0065] As an optional solution, the catalyst is selected from at least one of imidazole catalysts, pyridine catalysts, organic phosphorus catalysts, and metal salt catalysts.

[0066] As an optional solution, the imidazole catalyst is selected from at least one of 4-dimethylaminopyridine, 2-methylimidazole, 2-ethyl-4-methylimidazole, 2-phenylimidazole, modified imidazole, and zinc octoate.

[0067] As a further improvement of one embodiment of the present application, the resin composition further comprises 5 to 60 parts of a flame retardant based on solid weight.

[0068] As an optional solution, the flame retardant is at least one of a bromine flame retardant, a phosphorus flame retardant, a nitrogen flame retardant, an organosilicon flame retardant, and an organometallic flame retardant.

[0069] As an optional solution, the brominated flame retardant is selected from decabromodiphenyl ether, decabromodiphenyl ethane, brominated styrene or tetrabromophthalamide.

[0070] As an optional solution, the phosphorus flame retardant is selected from inorganic phosphorus, condensed phosphate compounds, phosphoric acid compounds, hypophosphorous acid compounds, phosphorus oxide compounds, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, 10-(2,5-dihydroxyphenyl)-9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, 10-phenyl-9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, tris(2,6-dimethylphenyl)phosphine, (m is an integer from 1 to 5), Phosphazene or modified phosphazene;

[0071] Among them, DOPO group is

[0072] Preferably, the phosphorus-based flame retardant is selected from condensed phosphate compounds, hypophosphorous acid compounds, and bis-DOPO compounds.

[0073] The present application also provides the use of the resin composition in prepregs, laminates, insulating boards, insulating films, circuit substrates and electronic devices.

[0074] Due to the application of the above technical solution, the present application has the following advantages compared with the prior art:

[0075] By modifying the maleimide resin with amine compounds and allyl compounds, and adding active ester compounds and epoxy resins, and controlling the content of low molecular weight components in the modified maleimide prepolymer, not only the compatibility between the maleimide resin, active ester and epoxy resin is improved, but also the heat resistance of the resin cured product is improved, and the dielectric properties and water absorption are reduced. DETAILED DESCRIPTION

[0076] The technical solution of the present application is further introduced below in conjunction with specific implementation methods. The following embodiments are merely descriptive and not restrictive, and the protection scope of the present application cannot be limited by them.

[0077] One embodiment of the present application provides a resin composition and the use of the resin composition in a prepreg, a laminate, an insulating board, an insulating film, a circuit substrate and an electronic device.

[0078] This embodiment provides a resin composition, measured by solid weight, comprising:

[0079] 20-100 parts of modified maleimide prepolymer;

[0080] 10-80 parts of epoxy resin;

[0081] 5-60 parts of active ester;

[0082] 5-50 parts of elastomer;

[0083] The reactants of the modified maleimide prepolymer include an amine compound, an allyl compound and a maleimide resin; and in the modified bismaleimide prepolymer, the mass proportion of the component with a number average molecular weight <1000 is 10% to 40%.

[0084] Preferably, in the modified bismaleimide prepolymer, the mass proportion of the component with a number average molecular weight <1000 is 10%, 15%, 20%, 25%, 30%, 35% or 40%.

[0085] Preferably, in the modified bismaleimide prepolymer, the component with a number average molecular weight <1000 is at least one of an amine-modified maleimide resin, an allyl-modified maleimide resin, and an allyl-amine-modified maleimide resin.

[0086] Preferably, the reactants of the modified maleimide prepolymer include, by solid weight: 1 to 50 parts of the amine compound; 5 to 60 parts of the allyl compound; and 100 parts of the maleimide resin.

[0087] More preferably, the reactants of the modified maleimide prepolymer include, by solid weight: 30 to 50 parts of the amine compound; 5 to 30 parts of the allyl compound; and 100 parts of the maleimide resin.

[0088] Preferably, the preparation method of the modified maleimide prepolymer comprises: dissolving and dispersing the amine compound, the allyl compound and the maleimide resin in an organic solvent, heating to 60°C to 150°C under nitrogen protection and keeping stirring, reacting for 0.5 to 5 hours, to obtain the modified bismaleimide prepolymer.

[0089] Preferably, in the preparation method of the modified maleimide prepolymer, the temperature is heated to 100° C. to 130° C. under nitrogen protection; and the reaction time is 1 h, 2 h, 3 h, 4 h or 5 h.

[0090] Optionally, the organic solvent is selected from at least one of acetone, butanone, methyl isobutyl ketone, ethylene glycol methyl ether, propylene glycol methyl ether, benzene, toluene, xylene, and cyclohexane.

[0091] Furthermore, the reactants of the modified maleimide prepolymer further include 0.5 to 10 parts of an aminophenol compound based on solid weight.

[0092] Preferably, the aminophenol compound is a p-aminophenol compound, a m-aminophenol compound or an o-aminophenol compound.

[0093] More preferably, the aminophenol compound is a p-aminophenol compound.

[0094] Optionally, the amine compound is selected from at least one of unsubstituted phenylenediamine, methylphenylenediamine, dimethylphenylenediamine, trimethylphenylenediamine, tetramethylphenylenediamine, xylene diamine, diaminopyridine, diaminodiphenylmethane, substituted diaminodiphenylmethane, bis[4-(4-aminophenoxy)phenyl]propane, bis[4-(4-aminophenoxy)phenyl]hexafluoropropane, diaminobenzophenone, diaminodiphenyl ether, diaminodiphenyl sulfone, diaminobiphenyl, diaminodiphenyl sulfide, diaminobinaphthyl, diaminodiphenylfluorene, diaminoanthraquinone, and amino-terminated silicone oil.

[0095] Preferably, the amine compound is selected from at least one of diaminodiphenyl ether, diaminodiphenyl sulfone, diaminodiphenylmethane and amino-terminated silicone oil.

[0096] Optionally, the allyl compound is selected from at least one of diallyl bisphenol A, diallyl bisphenol F, diallyl bisphenol S, allyl phenol oxide resin, allyl phenol formaldehyde resin and diallyl diphenyl ether.

[0097] Preferably, the allyl compound is diallyl bisphenol A.

[0098] Optionally, the maleimide resin is selected from at least one of the following structures:

[0099]

[0100] Me is methyl, Et is ethyl;

[0101] Me is a methyl group;

[0102] R1 is methylene or ethyl, R2 is hydrogen, methyl or ethyl, and n is an integer from 1 to 10;

[0103]

[0104] n is an integer from 1 to 10;

[0105] n is an integer from 1 to 10;

[0106] R is hydrogen, methyl or ethyl, and n is an integer from 1 to 10;

[0107] R is a methyl group, and n is an integer of 1-20.

[0108] The maleimide resin can be specifically selected from BMI-1000, BMI-2300, BMI-5100 or BMI-TMH manufactured by Yamato Chemical; BMI, BMI-70 or BMI-80 manufactured by KI Chemical; X9-470, X9-450 or X-9500 manufactured by DIC; MIR-3000 or MIR-5000 manufactured by Nippon Kayaku.

[0109] Preferably, the active ester contains an unsaturated double bond.

[0110] Optionally, the active ester is at least one of the following structures:

[0111]

[0112] Wherein, Ar is an aromatic group, Ar1 is an aromatic group and contains an unsaturated double bond substituent.

[0113] Preferably, the Ar group is a residue of a bisphenol structure, and Ar1 is a phenyl group or a naphthyl group containing an unsaturated double bond.

[0114] More preferably, the Ar group is a residue of bisphenol A, bisphenol F, bisphenol S, bisphenol E, dicyclopentadiene bisphenol, biphenyl bisphenol or naphthyl bisphenol.

[0115] Preferably, the bisphenol structure contains allyl or vinyl groups.

[0116] Optionally, the epoxy resin is selected from at least one of bisphenol A epoxy resin, bisphenol F epoxy resin, bisphenol S epoxy resin, bisphenol E epoxy resin, phosphorus-containing epoxy resin, o-cresol epoxy resin, bisphenol A novolac epoxy resin, phenol novolac epoxy resin, cresol novolac epoxy resin, triphenylmethane epoxy resin, tetraphenylethane epoxy resin, biphenyl epoxy resin, naphthalene ring epoxy resin, dicyclopentadiene epoxy resin, isocyanate epoxy resin, aralkyl linear phenolic epoxy resin, alicyclic epoxy resin, glycidyl amine epoxy resin, glycidyl ether epoxy resin, and glycidyl ester epoxy resin.

[0117] Preferably, the elastomer is at least one of styrene elastomer, acrylic elastomer, methacrylate elastomer, silicone elastomer, nitrile elastomer and core-shell rubber elastomer.

[0118] Preferably, the styrene-based elastomer is a hydrogenated or partially hydrogenated styrene-butadiene copolymer.

[0119] Specifically, the styrene-based elastomer is at least one of a hydrogenated or partially hydrogenated styrene-butadiene diblock copolymer and a hydrogenated or partially hydrogenated styrene-butadiene triblock copolymer.

[0120] The styrene elastomer can be specifically selected from SEPTON™ 2000 series (including 2002, 2004, 2005, 2006, 2063, 2104), SEPTON™ 4000 series (including 4033, 4044, 4055, 4077), HYBRAR TM 7000 series (including 7125, 7311), SEPTONTM 8000 series (including 8004, 8006, 8007L, 8851), SEPTONTM V series (including 9461, 9475), SEPTONTM Q1250; or, the styrene elastomer is selected from H1041, H1043, H1051, H1052, H1053, H1221 manufactured by Asahi Chemical Industry Co., Ltd.

[0121] As an optional solution, the acrylic elastomer and the methacrylic elastomer each independently contain at least one of the following structures:

[0122] Wherein, R1 is a C1-C5 alkyl group, and x is an integer from 1 to 100;

[0123] Wherein, R2 is a C1-C5 alkyl group, and y is an integer from 1 to 100;

[0124] Wherein, R3 is hydrogen or methyl, and o is an integer from 1 to 100.

[0125] More preferably, R1 is methyl, and R2 is methyl, ethyl or butyl.

[0126] The acrylic elastomer can be specifically selected from M51, M52, M22 or D51N manufactured by Arkema, LA2250, LA2140, LA-2330 or LA4285 manufactured by Kuraray Co., Ltd., SG-P3, SG-80H, PMS-22-1, PMS-22-4, PMS-19-5 or PMS-22-5 manufactured by Nagase, Japan.

[0127] The methacrylate elastomer can be specifically selected from M51, M52, M22 or D51N manufactured by Arkema, LA2250, LA2140, LA-2330 or LA4285 manufactured by Kuraray Co., Ltd., SG-P3, SG-80H, PMS-22-1, PMS-22-4, PMS-19-5 or PMS-22-5 manufactured by Nagase, Japan.

[0128] As an optional solution, the silicone elastomer comprises at least one of the following structures:

[0129]

[0130] Wherein, R is a C1-C12 hydrocarbon group or a C1-C12 alkoxy group; X is a mercapto group, an epoxy group, a hydroxyl group, a methoxy group or an amino group.

[0131] Preferably, R is methyl or phenyl.

[0132] Preferably, X is a mercapto group or an epoxy group.

[0133] The silicone elastomer can be specifically selected from SQ-20P or KHE-8000H produced by Nippon Kayaku, SQ502-8 produced by Arakawa Chemical, AY42-119 produced by DuPont Toray, X-40-2670, R-170S, X-40-2705, X-40-2701, KMP-600, KMP-605 or X-52-7030 produced by Shin-Etsu Chemical Co., Ltd., EP-2600, EP-2601, EP-2720, TMS-2670, EXL-2315 or EXL-2655 produced by DOW.

[0134] Furthermore, the resin composition further comprises 30 to 200 parts of inorganic filler based on solid weight.

[0135] Optionally, the inorganic filler is selected from at least one of non-metallic oxides, metal nitrides, non-metallic nitrides, inorganic hydrates, inorganic salts, metal hydrates or inorganic phosphorus.

[0136] Preferably, the inorganic filler is selected from at least one of fused silica, crystalline silica, spherical silica, hollow silica, aluminum hydroxide, aluminum oxide, talc, aluminum nitride, boron nitride, silicon carbide, barium sulfate, barium titanate, strontium titanate, calcium carbonate, calcium silicate, mica, and glass fiber powder.

[0137] More preferably, the inorganic filler is at least one of fused silica, crystalline silica, spherical silica, and hollow silica; more preferably, it is surface-treated spherical silica.

[0138] Furthermore, the inorganic filler is surface treated with a silane coupling agent, and the silane coupling agent is an epoxy-containing silane coupling agent, an amino-containing silane coupling agent, a vinyl-containing silane coupling agent, an acrylate-containing silane coupling agent, or an allyl-containing silane coupling agent.

[0139] Preferably, the median particle size of the inorganic filler is 1 to 15 microns, more preferably 1 to 10 microns.

[0140] Specifically, the median particle size of the inorganic filler is preferably 1 micron, 2 microns, 5 microns, 8 microns, 10 microns, 11 microns, 12 microns, 13 microns, or 14 microns.

[0141] Furthermore, the resin composition further comprises 0.01 to 8 parts of a catalyst based on solid weight.

[0142] Optionally, the catalyst is selected from at least one of imidazole catalysts, pyridine catalysts, organophosphorus catalysts, and metal salt catalysts.

[0143] Optionally, the imidazole catalyst is selected from at least one of 4-dimethylaminopyridine, 2-methylimidazole, 2-ethyl-4-methylimidazole, 2-phenylimidazole, modified imidazole, and zinc octoate.

[0144] Furthermore, the resin composition further comprises 5 to 60 parts of a flame retardant based on solid weight.

[0145] Optionally, the flame retardant is at least one of a bromine flame retardant, a phosphorus flame retardant, a nitrogen flame retardant, an organosilicon flame retardant, and an organometallic flame retardant.

[0146] Optionally, the brominated flame retardant is selected from decabromodiphenyl ether, decabromodiphenyl ethane, brominated styrene or tetrabromophthalamide.

[0147] Optionally, the phosphorus flame retardant is selected from inorganic phosphorus, condensed phosphate compounds, phosphoric acid compounds, hypophosphorous acid compounds, phosphorus oxide compounds, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, 10-(2,5-dihydroxyphenyl)-9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, 10-phenyl-9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, tris(2,6-dimethylphenyl)phosphine, (m is an integer from 1 to 5), Phosphazene or modified phosphazene;

[0148] Among them, DOPO group is

[0149] Preferably, the phosphorus-based flame retardant is selected from condensed phosphate compounds, hypophosphorous acid compounds, and bis-DOPO compounds.

[0150] The present application also provides a prepreg, comprising a reinforcing material and the aforementioned resin composition; the resin composition is wrapped on the reinforcing material.

[0151] The preparation method of the semi-cured sheet is as follows: the resin composition is dissolved in a solvent to prepare a glue solution, and then the glue solution is applied to the reinforcing material by an impregnation method, and the impregnated reinforcing material is taken out and baked at a temperature of 100 to 180° C. for 1 to 15 minutes; after drying, the semi-cured sheet can be obtained.

[0152] Optionally, the solvent is selected from at least one of acetone, butanone, methyl isobutyl ketone, N,N-dimethylformamide, N,N-dimethylacetamide, ethylene glycol methyl ether, propylene glycol methyl ether, benzene, toluene, xylene, and cyclohexane.

[0153] Optionally, the reinforcing material is selected from at least one of natural fibers, organic synthetic fibers, organic fabrics, and inorganic fabrics.

[0154] Preferably, the reinforcing material is glass fiber cloth. The glass fiber cloth is preferably open fiber cloth or flat cloth. More preferably, the glass fiber cloth is E glass fiber cloth, S glass fiber cloth or Q glass fiber cloth.

[0155] In addition, when the reinforcing material is glass fiber cloth, the glass fiber cloth is chemically treated with a coupling agent to improve the interface bonding between the resin composition and the glass fiber cloth. The coupling agent here is preferably an epoxy silane coupling agent or an amino silane coupling agent to provide good water resistance and heat resistance.

[0156] The present application also provides a laminate, comprising a piece of the aforementioned semi-cured sheet and a metal foil arranged on at least one side of the surface of the semi-cured sheet; or comprising a composite sheet formed by overlapping multiple pieces of the aforementioned semi-cured sheets and a metal foil arranged on at least one side of the surface of the composite sheet.

[0157] The preparation method of the laminate is: a metal foil is coated on one side or both sides of a prepreg, or at least two prepregs are stacked to form a combined sheet, a metal foil is coated on one side or both sides of the combined sheet, and a metal foil laminate is obtained by hot pressing. The pressing conditions of the hot pressing are: a pressure of 0.2 to 2 MPa, a temperature of 150 to 250° C., and a pressing time of 2 to 4 hours.

[0158] Preferably, the metal foil is selected from copper foil or aluminum foil. The thickness of the metal foil is 5 μm, 8 μm, 12 μm, 18 μm, 35 μm or 70 μm.

[0159] The present application also provides an insulating board, comprising the aforementioned resin composition.

[0160] The present application also provides an insulating film, comprising a carrier film and the above-mentioned resin composition coated thereon.

[0161] The insulating film is prepared by the following method: the resin composition is dissolved in a solvent to prepare a glue solution, the glue solution is then coated on a carrier film, and the carrier film coated with the glue solution is heated and dried to obtain the insulating film.

[0162] Optionally, the solvent is selected from at least one of acetone, butanone, methyl isobutyl ketone, N,N-dimethylformamide, N,N-dimethylacetamide, ethylene glycol methyl ether, propylene glycol methyl ether, benzene, toluene, xylene, and cyclohexane.

[0163] Optionally, the carrier film is selected from at least one of PET film, PP film, PE film and PVC film.

[0164] The present application also provides a circuit substrate, comprising at least one of the aforementioned prepreg, laminate, insulating plate, and insulating film.

[0165] The present application also provides an electronic device, comprising the aforementioned circuit substrate.

[0166] The technical solution of the present application is further described below in conjunction with some specific preparation examples, embodiments and comparative examples. Of course, these embodiments are only a part of the many variations of the embodiments of the present application, but not all.

[0167] Preparation Example 1

[0168] This preparation example prepares a modified maleimide prepolymer A, and the specific steps are as follows:

[0169] 50.0 g of amino-terminated silicone oil (manufactured by Shin-Etsu Chemical, X-22-161B), 110.0 g of diallyl bisphenol A, 200.0 g of maleimide resin (structural formula (1)), 180 g of N,N-dimethylformamide and 180 g of propylene glycol monomethyl ether were added to a 1 L reaction vessel equipped with a thermometer, a stirring device and a reflux condenser, and reacted at 120° C. for 4 h to obtain a solution of modified maleimide prepolymer A. Using gel permeation chromatography (GPC), according to the calibration curve of standard polystyrene, it was measured that the mass proportion of the component with a number average molecular weight of less than 1000 was 15%.

[0170] Preparation Example 2

[0171] This preparation example prepares a modified maleimide prepolymer B, and the specific steps are as follows:

[0172] 50.0 g of 3,3'-diaminodiphenylmethane, 110.0 g of diallyl bisphenol S, 200.0 g of maleimide resin (structural formula (3)), 180 g of N,N-dimethylformamide and 180 g of propylene glycol monomethyl ether were added to a 1 L reaction vessel equipped with a thermometer, a stirring device and a reflux condenser, and reacted at 130° C. for 3 h to obtain a solution of modified maleimide resin B. Using gel permeation chromatography (GPC), according to the calibration curve of standard polystyrene, it was measured that the mass proportion of the component with a number average molecular weight of less than 1000 was 35%.

[0173] Preparation Example 3

[0174] This preparation example prepares a modified maleimide prepolymer C, and the specific steps are as follows:

[0175] 50.0 g of 4,4'-diaminodiphenyl ether, 110.0 g of diallyl bisphenol A, 200.0 g of maleimide resin (structural formula (7)), 180 g of N,N-dimethylformamide and 180 g of propylene glycol monomethyl ether were added to a reaction vessel with a volume of 1 L equipped with a thermometer, a stirring device and a reflux condenser, and reacted at 120° C. for 4 h to obtain a solution of modified maleimide prepolymer C. Using gel permeation chromatography (GPC), according to the calibration curve of standard polystyrene, it was measured that the mass proportion of the component with a number average molecular weight of less than 1000 was 15%.

[0176] Preparation Example 4

[0177] This preparation example prepares a modified maleimide prepolymer D, and the specific steps are as follows:

[0178] 50.0 g of diaminodiphenylmethane, 110.0 g of diallyl bisphenol A, 200.0 g of maleimide resin (structural formula (8)), 180 g of N,N-dimethylformamide and 180 g of propylene glycol monomethyl ether were added to a reaction vessel with a volume of 1 L equipped with a thermometer, a stirring device and a reflux condenser, and reacted at 120° C. for 4 h to obtain a solution of modified maleimide prepolymer D. Using gel permeation chromatography (GPC), according to the calibration curve of standard polystyrene, it was measured that the mass proportion of the component with a number average molecular weight of less than 1000 was 15%.

[0179] Comparative Preparation Example 5

[0180] This preparation example prepares a modified maleimide prepolymer E, and the specific steps are as follows:

[0181] 50.0 g of amino-terminated silicone oil (manufactured by Shin-Etsu Chemical, X-22-161B), 110.0 g of diallyl bisphenol A, 200.0 g of maleimide resin (structural formula (1)), 180 g of N,N-dimethylformamide and 180 g of propylene glycol monomethyl ether were added to a 1 L reaction vessel equipped with a thermometer, a stirring device and a reflux condenser, and reacted at 120° C. for 2 h to obtain a solution of modified maleimide prepolymer E. Using gel permeation chromatography (GPC), according to the calibration curve of standard polystyrene, it was measured that the mass proportion of the component with a number average molecular weight of less than 1000 was 45%.

[0182] Example

[0183] The chemical components and contents of the resin compositions of Examples 1 to 4 and Comparative Examples 1 to 4 are shown in Table 1.

[0184]

[0185]

[0186] Among them, epoxy resin A is biphenyl type epoxy resin A made by Shengquan, epoxy resin B is naphthalene type HP-6000 made by DIC, active ester A is HP-8000 made by DIC, active ester B is prepared by the method in patent WO2018235425, active ester C is 3480P01 made by Kyoho, elastomer A is M51 made by Akema, elastomer B is SGP3 made by Nagano, the catalyst is 2-methylimidazole made by Shikoku Chemical, and the inorganic filler is spherical silica made by Lianrui, and the median particle size is 3 microns.

[0187] This embodiment also discloses a prepreg, comprising a glass fiber cloth as a reinforcing material and a resin composition coated on the glass fiber cloth by an impregnation method. The glass fiber cloth is a fiber-spreading cloth and is pretreated with an epoxy silane coupling agent;

[0188] Wherein, the prepreg is prepared by the following method:

[0189] The resin compositions of Examples 1 to 4 and Comparative Examples 1 to 4 were diluted with N, N-dimethylacetamide to form a glue solution with a solid content of 60 wt %;

[0190] The E glass fiber cloth used as the reinforcing material is pretreated with an epoxy silane coupling agent, immersed in the above-mentioned adhesive solution, taken out after being soaked, placed in a blast drying oven at 160° C., and baked for 3 to 6 minutes to obtain a semi-cured sheet.

[0191] This embodiment also discloses a laminate, which is prepared by the following method:

[0192] The above-mentioned semi-cured sheet was cut into 300×300mm, and then a 12μm thick electrolytic copper foil was placed on both sides of the semi-cured sheet, stacked into a certain stacking structure, placed in a vacuum hot press, and hot pressed for 4 hours at a pressure of 1.5MPa and a temperature of 200℃ to obtain a 1mm thick copper-clad laminate.

[0193] This embodiment also discloses an insulating board, including a prepreg sheet as described above, which is prepared by a conventional preparation method in the prior art, and will not be described in detail herein.

[0194] This embodiment also discloses a circuit substrate, including a prepreg sheet as described above, which is prepared by a conventional preparation method in the prior art, and will not be described in detail herein.

[0195] The copper-clad laminates obtained in Examples 1-4 and Comparative Examples 1-4 were subjected to performance testing, and the test results are shown in Table 2. The performance testing method includes:

[0196] (1) Glass transition temperature (Tg): The test was conducted using the DMA (thermomechanical analysis) method in accordance with IPC-TM-6502.4.25, with a heating rate of 10°C / min.

[0197] (2) Peel strength: The peel strength of the copper foil layer was tested according to the "after thermal stress" experimental conditions in IPC-TM-650 2.4.8 method.

[0198] (3) Tin immersion heat resistance: A 50×50 mm double-sided copper-clad laminate was immersed in 288°C solder and the time for the sample to delaminate and bubble was recorded.

[0199] (4) Tinning resistance (PCT, 6H): PCT (Pressure Cooking Test) 2atm, 121℃ cooking for 6h, then immersed in 288℃ solder, the tinning time is greater than 30min, and the time for the sample to delaminate and bubble is recorded.

[0200] (5) Water absorption after PCT 6H: After PCT cooking, the water absorption is calculated according to the method of IPC-TM-6502.6.2.1. Specifically, take 3 samples with a length × width of 10 cm × 10 cm, a thickness of 0.4 mm, and the electrolytic copper foil removed from both sides, dry them at 100°C for 2 hours, weigh them, and record the weight as W1. Then, treat them in a pressure cooker cooking tester at 121°C and 2 atmospheres for 2 hours, weigh them, and record the weight as W2. The water absorption is measured as (W2-W1) / W1×100%.

[0201] (6) X / Y axis thermal expansion coefficient (CTE): measured by TMA method in accordance with IPC-TM-650 method, with a heating rate of 10°C / min and a test temperature range of 30 to 100°C.

[0202] Table 2

[0203]

[0204] Referring to Table 1, compared with the comparative example, the resin composition of the embodiment of the present application not only has excellent compatibility, but also the copper clad laminate prepared therefrom has high heat resistance, low CTE and low water absorption.

[0205] It should be understood that although this specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each implementation mode may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

[0206] The detailed descriptions listed above are merely specific descriptions of feasible implementation methods of the present application. They are not intended to limit the scope of protection of the present application. Any equivalent implementation methods or changes that do not deviate from the technical spirit of the present application should be included in the scope of protection of the present application.

Claims

1. A resin composition, characterized in that By solid weight, including: 20-100 parts of modified maleimide prepolymer; 10-80 parts of epoxy resin; 5-60 parts of active ester; 5-50 parts of elastomer; The reactants of the modified maleimide prepolymer include an amine compound, an allyl compound and a maleimide resin; and in the modified bismaleimide prepolymer, the mass proportion of the component with a number average molecular weight <1000 is 10% to 40%.

2. The resin composition according to claim 1, characterized in that The reactants of the modified maleimide prepolymer include, by solid weight, 1 to 50 parts of the amine compound, 5 to 60 parts of the allyl compound, and 100 parts of the maleimide resin.

3. The resin composition according to claim 2, characterized in that The reactants of the modified maleimide prepolymer further include 0.5 to 10 parts of an aminophenol compound based on solid weight.

4. The resin composition according to any one of claims 1 to 3, characterized in that The amine compound is selected from at least one of unsubstituted phenylenediamine, methylphenylenediamine, dimethylphenylenediamine, trimethylphenylenediamine, tetramethylphenylenediamine, xylene diamine, diaminopyridine, diaminodiphenylmethane, substituted diaminodiphenylmethane, bis[4-(4-aminophenoxy)phenyl]propane, bis[4-(4-aminophenoxy)phenyl]hexafluoropropane, diaminobenzophenone, diaminodiphenyl ether, diaminodiphenyl sulfone, diaminobiphenyl, diaminodiphenyl sulfide, diaminobinaphthyl, diaminodiphenylfluorene, diaminoanthraquinone, and amino-terminated silicone oil.

5. The resin composition according to any one of claims 1 to 3, characterized in that The allyl compound is selected from at least one of diallyl bisphenol A, diallyl bisphenol F, diallyl bisphenol S, allyl phenol oxide resin, allyl phenol formaldehyde resin and diallyl diphenyl ether.

6. The resin composition according to claim 1, characterized in that The active ester contains an unsaturated double bond.

7. The resin composition according to claim 1, characterized in that The elastomer is at least one of styrene elastomer, acrylic elastomer, methacrylate elastomer, silicone elastomer, nitrile elastomer and core-shell rubber elastomer.

8. The resin composition according to claim 7, characterized in that The styrene-based elastomer is a hydrogenated or partially hydrogenated styrene-butadiene copolymer.

9. The resin composition according to claim 1, characterized in that Calculated by solid weight, 30 to 200 parts of inorganic filler are also included.

10. Use of the resin composition according to any one of claims 1 to 9 in prepregs, laminates, insulating boards, insulating films, circuit substrates and electronic devices.

Citation Information

Patent Citations

  • Active ester resin and composition and hardened substance using same

    WO2018235425A1

  • Halogen-free resin composition, and prepreg and laminated board prepared from same

    CN103965627A

  • Resin composition, prepreg, laminated board, metal foil cladded laminated board and printed circuit board

    CN110218415A

  • Resin composition and prepreg, insulating film, metal foil-clad laminate and printed circuit board having same

    CN112080102A

  • Resin composition as well as prepreg, laminated board and printed circuit board prepared from resin composition

    CN112250994A

Cited By

  • Modified maleimide prepolymer, resin composition and application thereof

    CN121471522A